Analisis Maqashid Al-Syari’ah terhadap Putusan Perdes No 1 Tahun 2009 tentang Kawasan Bebas Asap Rokok di Bone-Bone Kabupaten Enrekang - Yayu Dwi Lestari (PT PUSTAKA CENDEKIA GROUP, 2024)
In this study, the researcher used field research method. The type of descriptive qualitative research using data collection methods in this study is Observation, interviews and documentation with the aim of describing the sanctions for violators and the efforts of the village head in implementing a smoke-free area for the community in Bone-bone Village, Enrekang Regency. The results of this study indicate that the objectives of Village Regulation Number 1 of 2009 concerning the Smoke-Free Area in Bone-bone Village have been quite successful. This can be seen from the results of the study which show that 1) There is public awareness of the dangers of smoking, and there is a decrease in the number of smokers. 2) However, it is proven that there are still some people who smoke secretly such as in the garden and at home. 3) In addition, many people in Bone-Bone Village are aware of the impact of this regulation according to Maqashid al-Syariah, because Islam emphasizes the importance of maintaining health and avoiding all its harms. 4) And the impact of implementing the smoke-free area policy on health, economy, education, social relations in the community is quite positive. The implications of this study are 1) it is expected to provide theoretical benefits, as a material that can provide information to readers and can also be used as literature or references for other researchers. 2) which always provides a deep understanding of the impact or dangers of smoking are very positive steps.